Introduction. Histogenesis and classification: Round Table Testicular Tumors; coordinator Fabián Mendy Noriega - Mendy Noriega, Fabián (Cirugía del Uruguay, 1973)
Testicular tumors, although rare, are of great interest to the surgeon and urologist.